From Sanad to Syntax: The Disruption of Islamic Hermeneutics by Qur’anGPT - Mohammad Fattahun Niam (Basmala: Journal of Qur’an and Hadith, 2025)
Artificial Intelligence (AI) is increasingly encroaching upon domains once considered the exclusive purview of human cognition, including the interpretation of religious texts. While existing scholarship has explored the ethical and legal permissibility of AI within Islamic contexts, relatively little attention has been paid to how AI technologies—such as Qur’anGPT—are reshaping interpretive authority and hermeneutical methodologies. This article addresses that gap by critically examining Qur’anGPT as a case study of digital interpretive agency within contemporary Islam. This study employs a qualitative, literature-based methodology that integrates theoretical frameworks from digital hermeneutics with the sociology of Islamic knowledge. It is further complemented by a textual analysis of user interactions with Qur’anGPT. The findings suggest that Qur’anGPT functions not merely as a technological tool but as an epistemic actor, mediating Qur’anic meaning, shaping user perceptions, and reconfiguring traditional dynamics between scripture, scholars, and the community. Its algorithmic architecture and linguistic output indicate an emerging shift toward decentralized and democratized models of religious authority. However, this shift also raises critical concerns regarding interpretive reductionism, algorithmic bias, and the diminishing authority of classical epistemological frameworks, particularly those grounded in sanad and ijtihād. The study argues that while Qur’anGPT significantly improves access to Qur’anic texts, it may oversimplify complex theological discourses. Therefore, AI should be utilized as a supplementary tool—not as a replacement—for human interpretive judgment. The article concludes by proposing an ethical-theoretical framework for evaluating AI’s role in Islamic exegesis and presents implications for scholars, technologists, and religious institutions engaged at the intersection of Islam and digital innovation. [Kecerdasan Buatan (AI) semakin merambah ke dalam domain yang dulunya dianggap sebagai ranah eksklusif kognisi manusia, termasuk dalam interpretasi teks-teks agama. Meskipun penelitian yang ada telah mengeksplorasi kelayakan etis dan hukum AI dalam konteks Islam, perhatian yang relatif sedikit telah diberikan pada bagaimana teknologi AI—seperti Qur’anGPT—mengubah otoritas interpretatif dan metodologi hermeneutika. Artikel ini membahas kesenjangan tersebut dengan secara kritis mengkaji Qur’anGPT sebagai studi kasus agensi interpretatif digital dalam Islam kontemporer. Studi ini menggunakan metodologi kualitatif berbasis literatur yang mengintegrasikan kerangka teoretis dari hermeneutika digital dengan sosiologi pengetahuan Islam. Selain itu, studi ini dilengkapi dengan analisis tekstual terhadap interaksi pengguna dengan Qur’anGPT. Temuan tersebut menunjukkan bahwa Qur’anGPT berfungsi tidak hanya sebagai alat teknologi, tetapi juga sebagai aktor epistemik, yang memediasi makna Qur’an, membentuk persepsi pengguna, dan mengubah dinamika tradisional antara kitab suci, ulama, dan komunitas. Arsitektur algoritmik dan keluaran linguistiknya menunjukkan adanya pergeseran yang muncul menuju model otoritas religius yang terdesentralisasi dan terdemokratisasi. Namun, pergeseran ini juga menimbulkan kekhawatiran kritis mengenai reduksionisme interpretatif, bias algoritmik, dan berkurangnya otoritas kerangka epistemologis klasik, terutama yang didasarkan pada sanad dan ijtihād. Studi ini berpendapat bahwa meskipun Qur’anGPT secara signifikan meningkatkan akses ke teks-teks Qur’an, ia mungkin menyederhanakan diskursus teologis yang kompleks. Oleh karena itu, AI harus digunakan sebagai alat tambahan—bukan sebagai pengganti—untuk penilaian interpretatif manusia. Artikel ini diakhiri dengan mengusulkan kerangka etika-teoritis untuk mengevaluasi peran AI dalam eksgesis Islam dan menyajikan implikasi bagi para cendekiawan, teknolog, dan institusi keagamaan yang terlibat di persimpangan Islam dan inovasi digital.